Ruang Lingkup Kurikulum Pendidikan Agama Islam - Ulya, Ailia Niswatul Ulya; Kusmawati, Heny (PT Literasi Nusantara Publisher, 2023)
This research was conducted to determine the scope of the Islamic Religious Education curriculum and its development at the Madrasah Ibtidaiyyah level. By using a literature study, this research uses a variety of information from scientific sources regarding the development of the Islamic Religious Education curriculum. Education is a human process of becoming a perfect human being in which there are several long process sequences. Humans as God's creatures are equipped with reason to think and analyze the events that occurred during his life. The Islamic religion carries teachings that liberate humans from the shackles of ignorance to intelligent and noble human beings. Therefore, Islamic religious education becomes urgent to be studied in schools and implemented in everyday life. The curriculum used in the education unit determines the success or failure of an educational design, one of which is the Islamic religious education curriculum. Given the importance of this, it is necessary to review how to develop a curriculum that will bring religious education learning in accordance with the planned objectives.